Proximate determinants of infant mortality in Ethiopia, 2016 Ethiopian demographic and health surveys: results from a survival analysis - Masrie Getnet Abate; Dessie Abebaw Angaw; Tamrat Shaweno (BMC, 2020)
Abstract Background In Ethiopia, large scale health care efforts had been done to promote infant health and survival. However, nationwide data is lacking on the survival status and proximate determinants of infant mortality in Ethiopia. Therefore, this study was aimed to identify the survival status and determinants of infant mortality in Ethiopia using Ethiopian Demographic and Health Survey (EDHS). Methods The data source for this study was the 2016 Ethiopian Demographic and Health Survey. Records of all 10,641 live births and survival informations of all 2826 infants born 5 years before the survey were reviewed. Kaplan-Meier method and Cox proportional hazards regression model were employed to identify the proximate determinants associated with the infant mortality. Results The results of Kaplan-Meier estimation showed that the highest infant deaths occurred in the early months of life immediately after birth and declined in the later months of follow-up time. About 65% of infant deaths occurred during the first month's of life. Using the Cox proportional hazard model we found that: mothers' level of education, preceding birth interval, plurality, size of child at birth and sex of child as significant predictors of infant mortality. The risk of dying in infancy was lower for babies of mothers with secondary education (RR = 0.68, 95% CI: 0.56-0.98), higher education (RR = 0.51, 95% CI:0.45-0.80), for preceding birth interval longer than 47 months (RR = 0.51, 95% CI: 0.27, 0.92) and higher for birth interval shorter than 24 months (RR = 2.02, 95% CI:1.40-2.92), for multiple births (RR = 4.07, 95% CI: 1.14-14.50), for very small size of infants (RR = 3.74, 95% CI:1.73-8.12), for smaller than average size infants (RR = 3.23, 95% CI: 1.40-7.41) and for female infants (RR = 1.26, 95% CI: 1.01-1.56) compared to the reference category. Conclusions A significant proportion of infants died during the study period of which nearly two third of deaths occurred during the first months of life. Thus, close monitoring and supporting reproductive age mothers to increase the uptakes of family planning and antenatal care and follow-up is highly recommended to increase the infant survival.